اثر النشاط السياحي على سعر صرف الجنيه السوداني: خلال الفترة ١٩٩١ - ٢٠١٦م) - د. أسامة حسين محمد يوسف كب (White Nile Journal for Studies and Research, 2022)
This research aims to highlight the role played by tourism activity on the exchange rate of the Sudanese pound, and the research problem was represented in what is the impact of the tourism sector on the exchange rate in Sudan. The importance of the research was that tourism contributes greatly to the development of the state's financial resources, whether directly or indirectly. The objectives of the research are to highlight the real impact of tourism activity on the exchange rate, and the development of financial resources for the economy and the national economy. And to identify the problems facing tourism in Sudan. The hypothesis of the research is that there is an inverse relationship between the increase in tourism activity and the increase in the value of the national currency, the standard was used, by using the statistical package program (Eviews)), and data and information were obtained from primary sources and websites represented in tourism activity and the exchange rate from the Ministry of Tourism and reports The Central Bank of Sudan and it has been proven that there is an inverse relationship between tourism activity and the Sudanese pound exchange rate and that this relationship leads to a balance after five years. Continuing support for tourism in Sudan in a way that qualifies it to be one of the most important economic activities that provide job opportunities, through the application of policies that attract and qualify local labor and replace it with foreign labor in tourism activity. It is necessary to develop strategic plans and laws that must be implemented in the future In order to protect this activity